Myopia Control 2020: Where are we and where are we heading? - Bullimore, Mark A; Richdale, Kathryn (Ophthalmic & physiological optics, 2020)
Purpose This review arms practitioners with the evidence‐based information they need to fully manage myopia. Recent findings The recent peer‐reviewed literature is critically evaluated to provide a comprehensive analysis of the safety and efficacy of behavioural, optical and pharmaceutical myopia management. Importantly, the paper addresses not only who to treat, but how to treat them, and when to stop or modify treatments. Finally, the paper discusses expectations for treatment and why slowing myopia by even 1 dioptre improves long term health outcomes. Summary The management of an individual child should be underpinned by the evidence‐based literature and clinicians must stay alert to ongoing myopia research that will undoubtedly result in an evolution of the standard of care for the myopic and pre‐myopic child.